Mediação e conciliação judicial – formas alternativas de solução dos conflitos familiares - Costa, Luciana Vitalina Firmino da (2020)
This dissertation aims to approach mediation and judicial conciliation as alternative ways of solving family conflicts. At first, we deal with family legal disputes, the use of the family constellation, as well as the definition of conflict and the evolution of the concept of family. Then, we will discuss conciliation and mediation, including family mediation; its principles, peculiarities, advantages. Finally, we will deal with access to justice, attitudes of lawyers in the face of conciliation and mediation and the advantages of using conciliation and mediation techniques to resolve family legal conflicts.